Absorption of zinc and retention of calcium: Dose-dependent inhibition by phytate - Fredlund, Kerstin; Isaksson, Mats; Rossander-Hulthén, Lena; Almgren, Annette; Sandberg, Ann-Sofie (Journal of trace elements in medicine and biology, 2006)
The dose-dependent inhibitory effect of sodium phytate ( myo-inositol-hexaphosphate) on absorption of zinc and retention of calcium was studied in man. No systematic study of this dose–response effect has been reported to this time. Forty subjects were served meals containing white wheat rolls without/with additions of phytate. Ten subjects were given test meals containing one or two of the studied levels of phytate and in addition all subjects were served meals to which no phytate was added. The zinc content was 3.1 mg (47 μmol) and the calcium content 266 mg (6.6 mmol). The rolls were labelled extrinsically with radioisotopes, 65Zn and 47Ca, and whole-body retention of both minerals was measured. Totally 105 meals were served, 36 meals in which no phytate was added and 9–10 meals on each level of phytate. The zinc absorption in meals to which either 0, 25, 50, 75, 100, 140, 175 or 250 mg of phytate-P (0, 134, 269, 403, 538, 753, 941 or 1344 μmol phytate) had been added was 22%, 16%, 14%, 11%, 7%, 7%, 7% and 6%, respectively (mean values). The addition of 50 mg phytate-P or more significantly decreased zinc absorption ( p = 0.01 ) as compared to absorption from the test meals with no added phytate. The calcium retention at day 7 in the same meals was 31%, 28%, 27%, 26%, 22%, 19%, 14% and 11% (mean values). The addition of 100 mg phytate-P or more significantly decreased calcium retention ( p = 0.03 ) compared to the test meals with no added phytate. It was concluded that the inhibitory effect of phytate on the absorption of zinc and the retention of calcium was dose dependent.